Peningkatan Kreativitas Dengan Metode PBL Berbantuan Youtube Materi Hidup Milik Allah Fase F SMA Sedes Sapientiae Semarang - Paulus Bambang Tri Suwasono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Paulus Bambang Tri Suwasono. Increasing Creativity with PBL Method assisted by Youtube on the Material of Life Belonging to God in Phase E of Sma Sedes Sapientiae Semarang. The purpose of this study was to increase students' creativity in learning Catholic religion and ethics on the material of God's Life in Phase E of Sma Sedes Sapientiae Semarang in the 2023/2024 academic year through the application of the Problem Base learning model assisted by Youtube. This research was conducted at SMA Sedes Sapientiae Semarang. The research subject is class XI C phase F with 17 students who will be researched on the creative dimension of the Pancasila student profile through the Problem Base learning method. This type of research is a class action research (PTK). This research procedure consists of two cycles. The data collection tools used are teaching modules, observation sheets of the creative dimensions of the Pancasila student profile. The results showed that: the final average of the creative dimensions of students who took part in learning with the Problem Based Learning model in cycle I was 62.5; in cycle II the final average was 80.2 with an increase in the average score of 17.7. The results of this study indicate that learning using the Problem Based Learning model assisted by youutube is able to improve the creative dimension of the profile of better Pancasila students. Thus, the Problem Based Learning learning model assisted by YouTube has an effect on the creative thinking dimensions of phase F students of class XI SMA Sedes sapientiae Semarang.The success of learning using the Problem Base Learning method assisted by YouTube can be used as an alternative learning to improve the creative dimensions of the Pancasila student profile.